Application of biochar as an innovative substrate in constructed wetlands/biofilters for wastewater treatment: Performance and ecological benefits. (15th April 2021) - Deng, Shengjiong; Chen, Jinquan; Chang, Junjun
Abstract: Constructed wetlands (CWs) are well recognized as a cost-effective and environmentally friendly eco-technology for contaminated water remediation, especially in decentralized communities and rural areas. As a critical component in CWs, the substrate determines the wastewater treatment performance and ecological effects of CW systems. Biochar, a versatile and green carbonaceous biomaterial produced by carbonization of various biomasses, has recently been amended into CWs or biofilters (BFs) as a novel alternative substrate for wastewater treatment. In this paper, the performance of biochar amendment in CWs/biofilters with respect to the removal of nitrogen, phosphorus, organic contaminants, heavy metals and pathogens and its concurrent ecological benefits in improving macrophyte growth and mitigating greenhouse gas (GHG) emissions are summarized and evaluated. Furthermore, the mechanisms involved in these benefits, which are considerably different from those in batch tests, are analysed and elucidated, especially highlighting the roles of microorganisms. The high potential for recycling spent biochar media in CWs/BFs as a soil ameliorant/remediator is proposed. Collectively, it is highly promising to apply biochar as a substrate in CW/BF treatment systems, and more relevant research and practical applications of biochar substrates in CWs/BFs, especially the durability, recycling and possible negative effects of biochar, are required in the future. Graphical abstract: Image 1 Highlights: Biochar as an innovative substrate in constructed wetlands (CWs)/biofilters (BFs) for water treatment is reviewed. Biochar substrates enhance pollutant removal and mitigate greenhouse effect of CWs/BFs. Recycling spent biochar substrates into agrosystems can improve the sustainability of CWs/BFs. Scaling up application of biochar substrates is needed, taking care of potential negative effects.